Early Blight in Potato: Decade-Long Field Studies Show High Variation in Yield Losses - Erland Liljeroth; Linnea Stridh; Eva Edin; Radha Sivarajan Sajeevan (Potato Research, 2025)
The actual yield losses due to early blight disease in potato worldwide are not well described, and therefore, we analysed a decade-long series of field trials performed in Sweden. The series involved 18 trials with starch potato and six ware potato trials where early blight infection rate and yield were studied in untreated and fungicide-treated plots. Yield loss was estimated as the difference between the best fungicide strategy with respect to infection rate and untreated. The potential yield loss was calculated from the relationship between infection rate and yield. Yield and yield loss due to early blight were analysed in relation to weather and soil type. In starch potato, the variation in starch yield increase of fungicide-treated potato ranged from 1.9 to 29.9%, with an average of 11.9%. The calculated potential starch yield loss due to early blight was higher, 14.3% on average, reflecting minor infections in fungicide-treated plots. The large range of variation among trials indicates complex interactions among factors influencing infection rate and yield. We did not find any yield loss due to early blight in the ware potato trials. We found positive correlations between average season air temperature and infection rate in untreated plots. There was a negative correlation between average season air temperature and starch yield in both untreated and fungicide-treated plots. We also found a negative relationship between high soil sand content and infection rate. The yield increase due to fungicide treatment was higher on soils with high sand content. The calculated yield increase needed to compensate for the cost of early blight fungicide product sprayed in starch potato was approximately 250 kg starch per ha, corresponding to an approximately 2.7% yield increase. However, it is generally not economically feasible in Sweden to use fungicides against early blight in ware potato ready for harvest before the end of August.

Rapid emergence of boscalid resistance in Swedish populations of Alternaria solani revealed by a combination of field and laboratory experiments - Hadis Mostafanezhad; Eva Edin; Laura J. Grenville-Briggs; Åsa Lankinen; Erland Liljeroth (European Journal of Plant Pathology, 2022)
Early blight, caused by Alternaria solani , is a common potato disease worldwide. Reduced field efficacy of the fungicide boscalid against this disease has been reported in several countries. Boscalid resistance has been mostly studied with in-vitro and/or greenhouse experiments. Field studies validating this phenomenon are largely missing. Here, for the first time in Scandinavia, we validated boscalid resistance in a Swedish population of A. solani both in the field and in the laboratory. Field trials between 2014 and 2017 in Nymö showed significant efficacy reduction by year. The target regions of the A. solani genes encoding the succinate dehydrogenase subunits (Sdh) B, C and D of samples collected from Nymö, and additional fields in south-eastern and central Sweden, were analysed for substitutions associated with loss of boscalid sensitivity. In 2014, the SdhC-H134R mutation was found at several sites at a low frequency, while, in 2017, the majority of the samples had either the SdhB-H278Y or the SdhC-H134R substitution. No mutations were detected in the gene encoding the SdhD subunit. Spore germination tests showed a high sensitivity (EC 50 < 1 μg mL −1 ) of isolates lacking the substitutions. This was supported by a significant decrease in their radial growth rate, from 0.1 to 10 μg mL −1 boscalid. However, the mutated isolates had EC 50 > 100 μg mL −1 and their growth rates hardly decreased at concentrations above 1–10 μg mL −1 . These results add to the current knowledge of fungicide resistance development in field and indicate that early blight management in southeast Sweden should no longer rely on boscalid.

Additive effect of the root-lesion nematode Pratylenchus penetrans and the fungus Rhizoctonia solani on potato yield and damage - Maria Viketoft; Adam Flöhr; Jan-Eric Englund; Jonas Kardell; Eva Edin (Journal of Plant Diseases and Protection, 2020)
The significance of nematodes for disease development caused by other soil-borne pathogens has been demonstrated in many crops throughout the world and specifically prevalent are interactions between plant-parasitic nematodes and species of plant pathogenic fungi. Here, the interaction between the fungus Rhizoctonia solani (AG2) and the migratory endoparasitic root-lesion nematode Pratylenchus penetrans was investigated on potato. The hypotheses were that the combination of R. solani and P. penetrans would result in more severe canker lesions, reduced quality of the tubers and lower tuber yield, and we also expected higher nematode levels to render more nematode damage. To test this, potato plants were grown in pots in two replicate experiments and the presence and/or abundance of the two pathogens were controlled. The first three hypotheses were rejected as (1) the tuber yield decreased when the fungus and nematode occurred together but not more than the sum of their separate effects, i.e. additive, (2) there was no effect of presence of nematodes on the incidence of stem canker, and (3) the quality of tubers was actually partly improved as the presence of the nematodes reduced the likelihood of elephant hide on the tubers in one of the experiments. As expected, there were more visible nematode damages with addition of more nematodes, but beyond that the different nematode levels rendered in most cases similar responses. To have knowledge about interactions between pathogens, as the one showed here, is essential for disease control through appropriate management methods.

Within-season changes in Alternaria solani populations in potato in response to fungicide application strategies - Firuz Odilbekov; Eva Edin; Hadis Mostafanezhad; Hilde Coolman; Laura J. Grenville-Briggs; Erland Liljeroth (European Journal of Plant Pathology, 2019)

Cultivar Effects on the Interaction between Free-Living Plant-Parasitic Nematodes and the Fungal Pathogen Rhizoctonia solani in Potato - Maria Viketoft; Annhild Andersson; Eva Edin (American Journal of Potato Research, 2017)

Free-Living Plant-Parasitic Nematodes do not Affect the Efficiency of Seed Tuber Fungicide Treatment against Rhizoctonia solani - Eva Edin; Maria Viketoft (American Journal of Potato Research, 2017)